The Effect of Design Thinking Method Toward the Motivation of Visual Communication Design Students in Becoming an Entrepreneur - Sutadi, Agung Setiawan (VCD, 2022)
The world of work is a place of intense competition for each college graduate. Students are faced with developing new solutions to these problems/challenges so they need to practice identifying entrepreneurial opportunities so that the problem of the difficulty of competing in the world of work can be resolved with the emergence of new jobs. In the VCD department in the Visual Study subject using design thinking method as a study material in learning material with the aim of students being able to create a visual communication design that answers existing problems, so that ultimately students have a frame of mind in solving problems in running a business or facing client problems. Based on the results of data processing, the results show that there is a positive influence between design thinking methods on entrepreneurial motivation. Therefore, the role of design thinking methods in influencing student motivation to become entrepreneurs deserves further study. Keywords: Design, Design Thinking, Visual Study, Entrepreneur, Motivation